2010
DOI: 10.1111/j.1399-0004.2010.01406.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of germline AIP, MEN1, PRKAR1A, CDKN1B and CDKN2C mutations in causing pituitary adenomas in a large cohort of children, adolescents, and patients with genetic syndromes

Abstract: The prevalence of germline mutations in MEN1, AIP, PRKAR1A, CDKN1B and CDKN2CI is unknown among pediatric patients with pituitary adenomas (PA). In this study, we screened children with PA for mutations in these genes; somatic GNAS mutations were also studied in a limited number of growth hormone (GH) or prolactin (PRL)-secreting PA. We studied 74 and 6 patients with either isolated Cushing disease (CD) or GH-or PRL-secreting PA, respectively. We also screened 4 pediatric patients with CD, and 4 with GH/PRL-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
169
0
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(182 citation statements)
references
References 40 publications
8
169
0
5
Order By: Relevance
“…The tumors from AIPmut patients in a FIPA cohort were overwhelmingly macroadenomas (10). However, among 74 children with Cushing's disease, one AIP mutation was found in a patient diagnosed at the age of 6 years with a 3!4 mm ACTH-secreting adenoma (21). Subsequently, data are missing in the pediatric population to support the exclusion of children with microadenoma from the AIP genetic screening that we suggest in Fig.…”
Section: Marker Genomic Positionmentioning
confidence: 83%
See 2 more Smart Citations
“…The tumors from AIPmut patients in a FIPA cohort were overwhelmingly macroadenomas (10). However, among 74 children with Cushing's disease, one AIP mutation was found in a patient diagnosed at the age of 6 years with a 3!4 mm ACTH-secreting adenoma (21). Subsequently, data are missing in the pediatric population to support the exclusion of children with microadenoma from the AIP genetic screening that we suggest in Fig.…”
Section: Marker Genomic Positionmentioning
confidence: 83%
“…There are few data assessing the prevalence of MEN1 mutations in the specific case of isolated and sporadic macroadenoma. Stratakis et al (21) reported one MEN1 mutation in a 11-year-old male with macroprolactinoma among six patients with isolated GH-or PRL-secreting adenoma. In our study, MEN1 mutations were identified in 3.4% of cases and this frequency reaches 6.5% in the pediatric population (nZ3/46).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In sporadic pituitary adenomas, the occurrence of AIP mutations is much less frequent (17,18). However, it has been previously described that younger patients with somatotropinomas have a higher frequency of germline mutations, especially those less than 25 years old (19,20). Thus, it seems reasonable to screen young patients with apparently sporadic invasive somatotropinomas or prolactinomas for AIP mutations.…”
Section: Discussionmentioning
confidence: 99%
“…PRKAR1A mutations that lead to increased cAMP signaling, just like GNAS mutations, are responsible for gigantism or acromegaly in the context of Carney complex (CNC) but have never been found in sporadic GHPAs [4]. MEN1 (menin) gene mutations lead to gigantism and/or acromegaly in the context of multiple endocrine neoplasia (MEN) type 1 (MEN 1) but only rarely in sporadic acromegaly [5]. Mutations in the cyclin-dependent kinase (CDKN) 1B (CDKN1B) are found in MEN type 4 (MEN 4) [6]; other CDKNs, all essential molecules in the regulation of cell cycle, growth, and proliferation, are mutated, rarely, in MEN 1/MEN 4-like syndromic gigantism and/or acromegaly but not in sporadic GHPAs [7].…”
mentioning
confidence: 99%